Device free weekend - Doolittle, Sean, 1971- (Grand Central Publishing, 2023)
"Ryan Cloverhill, founder and CEO of the world's most popular social media platform, invites his six best friends from college to his home on his private island near Puget Sound. For Stephen, Emma, Perry, Will, Beau, and Lainie, day one is just what the doctor ordered: amazing food, many drinks, lots of laughter, and a sunset cruise around the island aboard their host's custom Van Dutch 55. Day two, however, takes a bewildering turn when the six hungover guests wake up to find that their host has disappeared, along with all connection to the mainland. A touchscreen tablet of unknown make awaits them, blatantly defying the rules of the weekend with its on-screen challenge: Unlock Me! The passcode to the tablet is hidden somewhere in the group's shared history. But what seems at first like just another silly game turns deadly serious when the group discovers what unlocking the tablet really means. Is it the key to their futures, a Pandora's box none of them will ever be able to close, or both? Only one thing is clear: their old friend Ryan has something unthinkable planned. Now it's up to the six of them to stop him. And when this weekend is over, the world will never be the same"--